2013
DOI: 10.5194/angeo-31-1843-2013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of meteor-head echo trajectories using the interferometric capabilities of MAARSY

Abstract: Abstract. During the flight of a meteoroid through the neutral atmosphere, the high kinetic energy is sufficient to ionize the meteoric constituents. Radar echoes coming from plasma irregularities surrounding the meteoroids are called meteor-head echoes, and can be detected by HPLA radar systems. Measurements of these echoes were conducted with MAARSY (Middle Atmosphere Alomar Radar System) in December 2010. The interferometric capabilities of the radar system permit the determination of the meteor trajectorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Though this paper focuses primarily on the nonspecular echoes, we first describe some of the features of the other echoes, since they provide us with additional information. Using the interferometry information on the head echo portion of the data [e.g., Chau and Woodman , , Schult et al , ], we found that the meteor entered Earth at a high geocentric speed of ∼69.5 km/s and came from ∼2 h 53 min right ascension, 29.47° declination, in modified ecliptic coordinates from the North Apex sporadic meteor source [ Chau et al , ]. Although the speed was large, the radial velocity was comparably slow due to the very low elevation angle (∼28.6°), therefore, it was observed over a long horizontal distance (∼50 km).…”
Section: Maarsy Nonspecular Meteor Echoesmentioning
confidence: 99%
“…Though this paper focuses primarily on the nonspecular echoes, we first describe some of the features of the other echoes, since they provide us with additional information. Using the interferometry information on the head echo portion of the data [e.g., Chau and Woodman , , Schult et al , ], we found that the meteor entered Earth at a high geocentric speed of ∼69.5 km/s and came from ∼2 h 53 min right ascension, 29.47° declination, in modified ecliptic coordinates from the North Apex sporadic meteor source [ Chau et al , ]. Although the speed was large, the radial velocity was comparably slow due to the very low elevation angle (∼28.6°), therefore, it was observed over a long horizontal distance (∼50 km).…”
Section: Maarsy Nonspecular Meteor Echoesmentioning
confidence: 99%
“…Interpreting these measurements requires a quantitative understanding of the structure of the neutral gas and plasma surrounding a meteoroid. This paper develops a first‐principle kinetic model aimed at interpreting head‐echo signals [ Bronshten , ; Ceplecha et al , ; Close et al , ; Pellinen‐Wannberg , ; Close et al , ; Dyrud and Janches , ; Campbell‐Brown and Close , ; Schult et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The MAARSY radar is one of the few radar systems that are capable of observing meteor head echoes as has been successfully demonstrated during the Geminids meteor shower in 2010 (Schult et al, 2013). Contrary to other radars that observed meteor head echoes on a campaign basis, MAARSY recently completed its second year of nearly continuous observations.…”
Section: Meteor Head Echo Observations With Maarsymentioning
confidence: 99%
“…Meteor head observations are described for various radar systems of sufficient power-aperture products, e.g. in Pellinen-Wannberg and Wannberg (1994), Janches et al (2000), Chau and Woodman (2004), Pellinen-Wannberg (2005), Chau et al (2009), Kero et al (2011) and Schult et al (2013).…”
Section: Introductionmentioning
confidence: 99%